Disaster Prevention from the Use of Plastic Waste with Ecobrick Project in Buluh Nipis Village - Permatasari, Silvia; Putri, Faradila; Hutagalung, Gracia TM; Rizal, Ibraldi; Innayah, Iffah; Zahara, Nindi; Tusa'diah, Risma; Nasywa, Sabila; Shatilla, Salwa Shabra; Sipahutar, Tegardo Natanael; Andri, Zaki Fadillah (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to investigate the effectiveness of eco-bricks in mitigating plastic waste pollution and to assess the impact of community socialization activities on promoting eco-brick usage in Buluh Nipis Village. It seeks to contribute to sustainable waste management practices and environmental conservation efforts. Method: Utilizing a participatory research approach, the study conducts socialization activities titled "Reusing Plastic Waste into Ecobricks that are Environmentally Friendly." Data collection methods include lectures, discussions, and practical demonstrations. Qualitative analysis is employed to understand community perceptions and attitudes toward eco-bricks. Practical Applications: By raising awareness and providing practical skills on ecobrick production, the study empowers residents to participate actively in plastic waste reduction efforts. The adoption of eco-bricks serves as a model for sustainable recycling practices and promotes environmental stewardship within the community. Conclusion: This research underscores the importance of community engagement in addressing plastic waste pollution. Promoting eco-bricks through targeted socialization activities contributes to sustainable waste management and environmental conservation initiatives at the local level.